School to Work Transition and Macroeconomic Conditions in the Turkish Economy - Ömer Tuğsal Doruk; Francesco Pastore (Institute of Labor Economics (IZA), 2020)
In emerging market economies, young people feel like little boats in the ocean, due to the low and uncertain macroeconomic context. In the present study, we examine the school-to-work transition in Turkey over the period 2014-2017 by using a monthly dataset. As most emerging market economies, the Turkish one faces a set of different macroeconomic conditions which make it a very hard task for many young graduates to find a job. We use panel logit models which allow studying the determinants of the probability of school-to-work transition completion with a time variant model. We look at such macroeconomic factors as GDP growth, industrial production index, real sector confidence index, real exchange rate and interest rate. In addition, we use some classifications for estimating the wage model for the new graduates and estimate by panel logit models the probability for young graduates of getting a white-collar job. Besides, the estimates are repeated for boom and bust periods, and in credit expansion periods.
Keywords: J64; O57; 330; school to work transition; macroeconomic conditions; developing economy; Turkish economy